Using The Think-Pair-Share (TPS) Strategy to Enhance Studentsâ Reading Achievement of The Seventh Grade at MTsN Lumpatan - Apriani, Eka (Sekolah Tinggi agama Islam Negeri (STAIN) Curup, 2016)
This study was aimed at investigating whether or not there was a significant difference in the studentsâ reading achievement after they were taught by using the Think Pair Share (TPS) strategy. A quasiexperimental design (non equivalent pre-test and post-test control design) was used in this study. Fifty six out of 145 seventh grade students of MTsN Lumpatan were purposively taken as the sample. There were 28 students in the experimental group and 28 students in the control group (N=56). The data was collected through reading test and analyzed by using t-test, multiple regression, and pearson product moment. The results showed the students who treated by using the Think-Pair-Share (TPS) strategy achieved a higher mean score of reading achievement (79.71) than the students who did not use the Think-Pair-Share (TPS) strategy. Keywords: Think-Pair-Share, Reading Achievement, MTsN Lumpatan